2010
DOI: 10.1111/j.1442-2042.2010.02569.x
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of antegrade radical prostatectomy for clinically locally advanced prostate cancer: a comparative study with clinically localized disease

Abstract: Objectives:To investigate intraoperative and early postoperative complications of antegrade radical prostatectomy with intended wide resection (aRP) for clinically locally advanced prostate cancer (cLAD) and to compare with those of aRP for clinically localized prostate cancer (cLD). Methods: Between March 1994 and June 2007, 800 consecutive Japanese patients including 625 with cLD and 175 with cLAD underwent aRP and bilateral limited lymphadenectomy. Clinicopathological data including intraoperative and early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Skilled surgeons performed RP and ePLND using either an open approach, minimal‐incision endoscopy, or robotic assistance. At our institution, limited lymph node dissection (LND) was the standard practice until 2012, when it was changed to ePLND 12,13 . In recent years, our institution has used the updated Briganti nomogram, and RP with ePLND was employed when the calculated probability of LNM exceeded 7% 14 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Skilled surgeons performed RP and ePLND using either an open approach, minimal‐incision endoscopy, or robotic assistance. At our institution, limited lymph node dissection (LND) was the standard practice until 2012, when it was changed to ePLND 12,13 . In recent years, our institution has used the updated Briganti nomogram, and RP with ePLND was employed when the calculated probability of LNM exceeded 7% 14 …”
Section: Methodsmentioning
confidence: 99%
“…At our institution, limited lymph node dissection (LND) was the standard practice until 2012, when it was changed to ePLND. 12,13 In recent years, our institution has used the updated Briganti nomogram, and RP with ePLND was employed when the calculated probability of LNM exceeded 7%. 14 The data collected included patient age at surgery, initial prostate-specific antigen (PSA) level, biopsy Gleason score (GS), number of biopsy cores taken, digital rectal examination (DRE) findings, MRI findings, and final RP pathology including pathological T and N stage.…”
Section: Introductionmentioning
confidence: 99%
“…Imaging studies preoperatively confirmed that all patients had no metastases. Skilled surgeons performed RP and ePLND (including external, internal iliac, and obturator lymph nodes) using either an open or minimum incision endoscopic or robot-assisted approach [ 14 , 15 ]. The probability of LNI was evaluated using the Briganti 2019 nomogram [ 7 ], Briganti 2017 nomogram [ 16 ], Briganti 2012 nomogram [ 17 ], MSKCC nomogram [ 18 ], Partin 2017 nomogram [ 19 ], and Japan PC table [ 20 ], based on clinical data and biopsy results (Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The authors performed antegrade radical prostatectomy with wide resection of neurovascular bundles, bladder neck, and complete resection of Denonvilliers' fascia for patients with clinically locally advanced prostate cancer. These procedures are often associated with tedious bleeding from perirectal adipose tissue; however, the authors obtained satisfying surgical results and described their feasibility and safety in the study 1 …”
mentioning
confidence: 99%